CHIP FORMATION DURING THERMAL FRICTION TURN-MILLING - Mussayev, Medgat; Sherov, Karibek; Taskarina, Aizhan; Sherov, Aybek; Gabdyssalik, Riza; Buzauova, Toty; Ainabekova, Saule (Journal of Applied Engineering Science, 2020)
This paper presents the results of chip formation studies in the processing of 30KhGSA steel by thermofriction turn-milling. When studying the process in this work there are presented the results of studying chip formation when the processing of chip formation there is used the metallographic method. Chip root area investigated. The dependence of the chip shrinkage coefficient on the cutting speed and feed was also investigated. It is established that with increasing supply S the value of the chip shrinkage coefficient K decreases. The higher the chip shrinkage factor, the more work will be required to cut the chips and the more complex the processing process.